Dieta enriquecida com lipídeo associada à somatotropina recombinante bovina em novilhas superovuladas - Oliveira, Richelle Matos (2021)
The aim was to evaluate the effects of soybean oil supplementation associated with the administration of bovine recombinant somatotropin (rBST) on the population of ovarian follicles, standardization of the superovulation response, and embryo recovery. We used 40 Holstein heifers submitted to a 2x2 factorial, with two diets, without or with soybean oil supplementation; and the administration or not of rBST seven days after estrus, forming the experimental groups: DC-SL (control diet plus saline solution application); OL-SL (diet with soybean oil plus saline application); DC-rBST (control diet plus application of 320 mg rBST) e OL-rBST (diet with soybean oil plus the application of 320 mg rBST). The animals received two applications of 500 mg of PGF2α for estrus synchronization and were superovulated with 400 IU of FSH in decreasing daily doses for four consecutive days. On the day before the start of superovulation, the two largest follicles were punctured to quantify the intrafollicular concentration of high-density lipoprotein (HDL). Statistical analyzes were processed using the Action R statistical software version 3.0.2, using ANOVA and Fisher's Test (F test; two comparisons) for the mean characteristics with a probability level of 5%. There were no differences in dry matter intake, follicular activity, P4 concentration, and superovulation response. The group OL-rBST got a greater CL area (4.67±0.67 cm2) and a positive effect was evidenced for HDL concentration in the treatment groups OL-SL (40.86±9.8 mg/dL) and OL-rBST (53.67±10.35 mg/dL). Soybean oil supplementation in the diet associated with the administration of rBST did not provide uniformity in the superovulation response and the embryonic recovery of heifer.